IMPLEMENTING ROUNDTABLE COMBINED WITH PICTURE TO IMPROVE WRITING SKILL OF THE EIGHTH-GRADE STUDENTS OF SMPN 6 DENPASAR IN THE ACADEMIC YEAR 2022/2023 - Hani Bunga Laely; Anak Agung Putri Maharani; I Komang Budiarta (Academic Journal on English Studies (AJOES), 2023)
The undertaking of the exploration was substantially grounded on the primary study. The result of pre-test showed that utmost of the scholars in VIII-4 class of SMPN 6 Denpasar in academic year 2022/2023 faced problem in writing skill. The students had problems in constructing unified and coherent writing descriptive paragraph. The subjects consisted of 41 students: 20 males and 21 females. The object was to know whether or not the writing skill of the eighth-grade students of SMPN 6 Denpasar in academic year 2022/2023 can be improved trough Roundtable combined with picture. The design was a classroom behavioral study. This was done in two cycles, each cycle consisting of two sessions. Data showed that there were significant improvement on subject's average score from pre- and post-tests. The average pretest score was 45.39, post-test I was 74.39, and posttest II was 83.73. As supporting data, the questionnaire was also administered at the end of the last cycle and the results were displayed more than 93% of the subjects positively agreed on implementing Roundtable combined with picture in improving writing skill. Based on the data, the implementation of Roundtable combined with picture can make the subject more creative and be brave in expressing their idea into a good paragraph. Based on the findings, it could be concluded that the writing ability of the eighth-grade students at SMPN 6 Denpasar in the 2022/2023 school can be improved trough a Roundtable combined with picture.